1997
DOI: 10.1063/1.120181
|View full text |Cite
|
Sign up to set email alerts
|

Faraday rotation in magnetic γ-Fe2O3/SiO2 nanocomposites

Abstract: Faraday rotation spectrum has been measured at room temperature in a magnetic nanocomposite of γ-Fe2O3/SiO2. The material consists of isolated γ-Fe2O3 nanoparticles dispersed in a silica matrix, and it was prepared through a sol-gel method. The composite contains 18% of γ-Fe2O3 in weight with an average particle size of 20 nm. It has a coercitivity of 30 Oe and an MS of 6 emu/g. The specific Faraday rotation spectrum exhibits a narrow peak centered around 765 nm, reaching a value of 110°/cm and an absorption c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 13 publications
1
42
0
Order By: Relevance
“…6) with a specific maximum rotation of 26 cm ±1 and an equivalent Verdet constant (i.e., maximum slope in the rotation curve) of 0.0548 G ±1 cm ±1 (1 G = 1 Oe = 10 ±4 T). The Faraday rotation values are of the same order of magnitude as those obtained in c-Fe 2 O 3 /SiO 2 samples prepared by the sol±gel method [13] (about 90 cm ±1 ) with much lower iron concentration (10.4 wt.-% c-Fe 2 O 3 in the Vycor composite versus 19.3 in sol±gel samples) [18] and smaller particle size (11 nm versus 20 nm). The larger particle size in the composite prepared via sol±gel lead to samples with much larger coercivity, which prevents the composites from being used in low magnetic-field sensors.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…6) with a specific maximum rotation of 26 cm ±1 and an equivalent Verdet constant (i.e., maximum slope in the rotation curve) of 0.0548 G ±1 cm ±1 (1 G = 1 Oe = 10 ±4 T). The Faraday rotation values are of the same order of magnitude as those obtained in c-Fe 2 O 3 /SiO 2 samples prepared by the sol±gel method [13] (about 90 cm ±1 ) with much lower iron concentration (10.4 wt.-% c-Fe 2 O 3 in the Vycor composite versus 19.3 in sol±gel samples) [18] and smaller particle size (11 nm versus 20 nm). The larger particle size in the composite prepared via sol±gel lead to samples with much larger coercivity, which prevents the composites from being used in low magnetic-field sensors.…”
mentioning
confidence: 73%
“…It is important to reduce the size of the magnetic particles in the composite in order to obtain superparamagnetic behavior allowing the sample to be used as a low magnetic field sensor. Guerrero et al [13] observed Faraday rotation in c-Fe 2 O 3 /SiO 2 samples, in which the iron oxide particles grew during the formation of the sol±gel silica matrix. These magnetic and transparent composites comprise particles with a mean size around 20 nm, which exhibit large coercivity and prevent their use in low-field magnetic sensors.…”
mentioning
confidence: 97%
“…Taken into account the spontaneous magnetization of maghemite (Ms = 370 kA/m), from the values of the average magnetic moment of particles, it is possible to estimate the size of such nanoparticles, if they are considered as spherical, from the relationship: (2) Looking at the TEM micrographs, this assumption seems to be a good approximation.…”
Section: Resultsmentioning
confidence: 99%
“…Nanocomposites made up of particles embedded in a porous matrix have attracted considerable interest, since the structural confinement of the nanoparticles allows tailoring their physical properties [1,2]. A porous matrix provides, at the same time, enough nucleation sites for nanoparticle formation and an effective way to avoid their aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…The sol-gel methods have been used to prepare the nanocomposites containing ferrite nanoparticles dispersed in a silica matrix including NiFe 2 O 4 [2][3][4][5][6] , ZnFe 2 O 4 [7][8][9] , CdFe 2 O 4 [9] , CuFe 2 O 4 [6] , CoFe 2 O 4 [6,[10][11][12][13][14] , Ni-Zn ferrite [15] , Mn-Zn ferrite [16] , and γ-Fe 2 O 3 [17][18][19][20][21][22][23][24] , among which γ-Fe 2 O 3 /SiO 2 is a well-established example. It was found that many experimental parameters could influence the properties of γ-Fe 2 O 3 /SiO 2 [17][18][19][20][21][22][23][24] . Even though increasing efforts have been devoted to the preparation of nanocomposites for other ferrites dispersed in silica matrix [2][3][4][5][6][7][8][9][10][11][12][13][14][15]…”
Section: Introductionmentioning
confidence: 99%